Institutions: Definition, Attributes and Research Areas - G. B. Kleiner (Управление)
The author explores the essence and content of the concept of «institute» in terms of the different approaches of contemporary institutional theory. The author shows the relationship of institutions with cultural, social, legal norms, norms of behavior, routines, and habits. The author offers his own original picture of the institutional architecture of the socio-economic system and proves subsequent research areas of institutional economics.